2015
DOI: 10.3390/ijerph13010012
|View full text |Cite
|
Sign up to set email alerts
|

PVT1 Exon 9: A Potential Biomarker of Aggressive Prostate Cancer?

Abstract: Prostate cancer (PCa) is the most commonly diagnosed cancer as well as the greatest source of cancer-related mortality in males of African ancestry (MoAA). Interestingly, this has been shown to be associated with single nucleotide polymorphisms around regions 2 and 3 of the 8q24 human chromosomal region. The non-protein coding gene locus Plasmacytoma Variant Translocation 1 (PVT1) is located at 8q24 and is overexpressed in PCa and, therefore, is also a candidate biomarker to explain the well-known disparity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
1
33
0
2
Order By: Relevance
“…Plasmocytoma variant translocation 1 (PVT1) is a long nonprotein-coding gene located at the 8q24 human chromosomal region and is commonly dysregulated in PCa [5,6]. The PVT1 gene locus is comprised of at least twelve exons, which gives rise to several alternatively spliced nonprotein coding transcripts, and encodes six microRNAs: miR-1204, miR-1205, miR-1207-3p, miR-1207-5p, and miR-1208 [7]. PVT1 has been found to be overexpressed in various cancers including breast, lung, colorectal, ovarian, and PCa [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmocytoma variant translocation 1 (PVT1) is a long nonprotein-coding gene located at the 8q24 human chromosomal region and is commonly dysregulated in PCa [5,6]. The PVT1 gene locus is comprised of at least twelve exons, which gives rise to several alternatively spliced nonprotein coding transcripts, and encodes six microRNAs: miR-1204, miR-1205, miR-1207-3p, miR-1207-5p, and miR-1208 [7]. PVT1 has been found to be overexpressed in various cancers including breast, lung, colorectal, ovarian, and PCa [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PVT1 is overexpressed in prostate cancer tumor tissues and is associated with regulating tumor growth (8,9). It has been shown that PVT1 exon 9 is significantly overexpressed in aggressive prostate cancer cell lines derived from AA men (10). PVT1 is a long noncoding RNA and is the host to a cluster of miRNAs (such as miR-1204, miR-1205, and miR-1206; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Knock down of PVT1 exons 4A and 4B in turn did not yield similar effects. The Ogunwobi laboratory also reported that PVT1 exon 9 is significantly overexpressed in prostate cancer cell lines derived from men of African Ancestry (MoAA) (94) (Figure 3). This observation was made from comparing the relative expression of PVT1 exons in different cell lines derived from men of different ethnic and racial backgrounds.…”
Section: Pvt1 In Prostate Cancermentioning
confidence: 93%